Selecting measures for the neurodevelopmental assessment of children in low- and middle-income countries. Issue 7 (3rd October 2017) - Semrud-Clikeman, Margaret; Romero, Regilda Anne A.; Prado, Elizabeth L.; Shapiro, Elsa G.; Bangirana, Paul; John, Chandy C.
ABSTRACT: Diseases affecting millions of children in low- and middle-income countries (LMICs), such as malnutrition, micronutrient deficiency, malaria, and HIV, can lead to adverse neurodevelopmental outcomes. Thus, a key health outcome in children is neurodevelopmental status. In this paper, the neurodevelopmental screening and testing measures most commonly utilized in LMICs are reviewed, and a matrix is presented to help researchers and clinicians determine which measures may be most useful for various LMIC inquiries. The matrix is based on an Internet literature review of 114 publications for the period January 1998 to February 2016, reporting the psychometric properties of instruments tested in LMIC children. The measures are classified as screening tests or more detailed tests that include both comprehensive batteries of general development and tests of specific domains. For completeness, two experts have reviewed this paper, as well as the authors. An overview of the tests used to date is presented, including the benefits and drawbacks of each test, in order to provide researchers and developmental clinicians with a way to decide which tests may be best suited to their developmental assessment goals. Remarkable progress has been made in neurodevelopmental testing in children in LMICs over the past two decades but there remains a need for additional research in this area to develop new tests, better evaluate and adapt current tests, and assess test validity and reliability across cultures.